HISTOLOGICAL AND BIOCHEMICAL EFFECTS OF ENDOSULFAN AND MALATHION ON RAT TESTIS - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2008)
This study was conducted to assess the invivo effects of the endosulfan and malathion on the testis tissues of rats. Endosulfan and malathion are two of the most widely used insecticides throu-hout the world. During the study, combinations of low and high doses of endosulfan and malathion were administrated intraperitoneally to the male rats for 15 days. It is suggested that endosulfan and malathion have some histolooical and biochemical damaues and toxic effects in testis tissues of rats.
Keywords: Endosulfan; malathion; rat; testis; MALONDIALDEHYDE DETERMINATION